2015
DOI: 10.1016/j.ajhg.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Paired-Duplication Signatures Mark Cryptic Inversions and Other Complex Structural Variation

Abstract: Copy-number variants (CNVs) have been the predominant focus of genetic studies of structural variation, and chromosomal microarray (CMA) for genome-wide CNV detection is the recommended first-tier genetic diagnostic screen in neurodevelopmental disorders. We compared CNVs observed by CMA to the structural variation detected by whole-genome large-insert sequencing in 259 individuals diagnosed with autism spectrum disorder (ASD) from the Simons Simplex Collection. These analyses revealed a diverse landscape of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 32 publications
7
61
0
Order By: Relevance
“…9, 10). Statistically significant CNV segments were integrated with predicted balanced SVs using a series of breakpoint linking methods to identify signatures of 20 canonical, balanced, and complex SV classes (Supplementary Table 8) 27,30 .…”
Section: Resultsmentioning
confidence: 99%
“…9, 10). Statistically significant CNV segments were integrated with predicted balanced SVs using a series of breakpoint linking methods to identify signatures of 20 canonical, balanced, and complex SV classes (Supplementary Table 8) 27,30 .…”
Section: Resultsmentioning
confidence: 99%
“…All computational analyses have been previously described 74,83 . In brief, reads were reverse-complemented and aligned using BWA 84 .…”
Section: Methodsmentioning
confidence: 99%
“…Anomalous read-pairs in terms of insert size, mate mapping, or mate orientation were extracted using Sambamba and clustered using ReadPairCluster, our single-linkage clustering algorithm 11,85 . Anomalous read-pair clusters meeting our established thresholds of structural variation were subsequently classified based on their read-pair orientation signature into the following categories: deletions, insertions, inversions, and translocations 83 . When no clusters were found that matched the proposed karyotype, BAM files were agnostically analyzed and manually inspected for anomalous pairs or split reads.…”
Section: Methodsmentioning
confidence: 99%
“…The spectrum of SVs present in gnomAD-SV was diverse: we completely resolved 5,295 complex SVs across 11 mutational subclasses, of which 3,901 (73.7%) involved inverted segments (Figure 2), confirming prior predictions that most inversion variation accessible to short-read WGS comprises complex SVs rather than canonical inversions. 1,30 Across all SV classes, most SVs were small (median SV size = 331 bp; Figure 1f) and rare (AF < 1%; 92% of SVs; Figure 1g), with nearly half of all SVs (49.8%) appearing as "singletons" (i.e., only one allele observed across all samples). While singleton proportion varied by SV class, it was strongly dependent on SV size across all classes, suggesting that the amount of genetic material rearranged is a principal determinant of selection against most SVs (Figure 1h and Extended Data Figure 5a).…”
Section: Figure 1 | Properties Of Svs Across Human Populationsmentioning
confidence: 99%